Intravascular Mesenchymal Chondrosarcoma of the Femoral Vein: A Case Report. Issue 3 (July 2021) - Sabharwal, Samir; Fayad, Laura M.; McCarthy, Edward F.; Morris, Carol D.
Abstract : Case: A 30-year-old man presented with progressive lower right extremity pain and swelling, initially diagnosed as a deep venous thrombosis. He returned 18 months later after 2 episodes of gross hemoptysis, with chest computed tomography angiography findings concerning for tumor thrombus in the left pulmonary artery. Subsequent advanced imaging showed a lesion arising from his right femoral vein, which open biopsy revealed to be a primary intravascular mesenchymal chondrosarcoma. He underwent medical therapy, with improvement of pain and swelling and successful return to work. Conclusion: Mesenchymal chondrosarcoma is a rare pathology, and its intravascular origin makes this case extraordinarily uncommon.